Unsteady Electrohydrodynamic Stagnation Point Flow of Hybrid Nanofluid Past a Convective Heated Stretch/Shrink Sheet. (29th October 2021) - Jawad, Muhammad; Jan, Rashid; Boulaaras, Salah; Amin, Ibni; Shah, Niaz Ali; Idris, Sahar Ahmed
Abstract : Unsteady electrohydrodynamic hybrid nanofluid Al 2 O 3 ‐ Cu / H 2 O past a convective heat stretched/shrinked sheet is examined. A stagnation point fluid flow with velocity slip constrains and heat source or sink is deliberated. The combined set of PDEs is translated into ODEs by including approved similarity transformations. HAM is applied for the solution to the obtained nonlinear system. The magnetic input factor, Prandtl number, electric field factor, Eckert number, heat source factor, and unstable factor are the governing parameters. The impact of these factors on the temperature and velocity profiles features of the problem is considered with explanation. Intensification in values of electric and magnetic fields parameters enhanced the heat transfer rate. The greater Prandtl number lessens the temperature. Amplification in temperature is perceived for Eckert parameter. The heat transferred rate of hybrid nanofluid in the entire domain increases as the heat source increases, while the heat sink has the opposite effect. Skin friction and Nusselt number is increased for increasing values of magnetic field parameters. It is also noted that Nusselt number lessens for raising in Pr, E, and   Ec . Furthermore, it is eminent that the hybrid nanofluid possesses better result compared to the nanofluid.